Выражения: а) (2х -3)(4х+1) б) (3х-у)(2у-7х) в) а(а+-2)(а+6) г) (1-3b)(9b во 2 степени + 3и +1)

ludafrolova98 ludafrolova98    3   26.02.2019 23:20    1

Ответы
alexcopes4 alexcopes4  23.05.2020 15:10

а) (2x - 3)(4x + 1) = 8x² - 12x + 2x - 3 = 8x² - 10x - 3

б) (3x - y)(2y - 7x) = 6xy - 2y² - 21x² + 7xy = -2y² + 13xy - 21x²

в) a(a + 4) - (a - 2)(a + 6) = a² + 4a - (a² - 2a + 6a - 12) =

= a² + 4a - a² + 2a - 6a + 12 = 12

г) (1 - 3b)(9b² + 3b + 1) = 9b² - 27b³ + 3b - 9b² + 1 - 3b =

= -27b³ + 1 = 1 - 27b³

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра